Efektivitas Penggunaan Antibiotik Golongan Sefalosporin Pada Terapi Demam Tifoid Pediatri Rawat Inap - Zalfa, Saniyyah; Muthoharoh, Ainun; Rahmatullah, St.; Ningrum, Wulan Agustin (Universitas Muhammadiyah Pekajangan Pekalongan, 2024)
Typhoid fever is caused by an infection with the bacterium Salmonella typhi. Typhoid fever remains a public health issue around the world, particularly in developing countries with inadequate sanitation and high population density. The achievement of the desired treatment regimen is indicated by treatment efficacy. Irrational drug use can make treatment ineffective. The antibiotics used are third generation cephalosporins. The purpose of this study was to determine the risk factors and effectiveness of thirdgeneration cephalosporin antibiotics in pediatric typhoid fever patients based on the type of antibiotic used, length of treatment, and fever-free time. This study is designed as prospective cross-sectional research with total sampling, where interviews are conducted with patients and medical record data is reviewed. Data analysis was conducted using both univariate and bivariate methods, employing the Independent T-test and MannWhitney statistical tests with SPSS version 16. Typhoid fever patients were male (67.6%) and female (32.4%). The majority of patients (67.6%) were aged 5 to 13 years. A habit of random snacking poses the highest risk, accounting for 91.1%. Mann-Whitney test showed a significant result for length of treatment days (p-value < 0.001). Similarly, independent t-test for Fever-free time showed p-value = 0.01 (< 0.05). In conclusion, ceftriaxon antibiotics are more effective than cefixime with a significant difference